Stockholm 1917 : Camille Huysmans in de schaduw van titanen - Geldolf, Wim (Antwerpen : Contact, 1996)
Bibliotheek François Vercammen
Nederlands
Monografie
Keywords: Huysmans, Camille; De Geyter, Pierre; Wereldoorlog 1